Diabetic Eye Disease - From Therapeutic Pipeline to the Real World 2022
DOI: 10.5772/intechopen.99904
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipid, Protein-Derived Toxic Molecules, and Deficiency of Antioxidants behind the Pathogenesis of Diabetic Retinopathy (DR) in Type 2 Diabetes Mellitus

Abstract: To determine the role of NADPH-oxidase mediated formation of different lipid, protein-derived molecules, and depletion of vitamin-C level in vitreous behind the endothelial dysfunction-induced vascular endothelial growth factor secretion and pathogenesis of diabetic retinopathy (DR) in type 2 diabetes mellitus (T2DM). Fourteen T2DM patients with mild non-proliferative diabetic retinopathy (MNPDR), 11 patients without diabetic retinopathy (DNR), 17 T2 DM subjects with high-risk proliferative diabetic retinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It has been demonstrated by landmark studies that improving glycemic control reduces the risk of development and progression of DR, though there is no lower limit of glycemic control that is protective against the onset of retinopathy [15,16]. Our sequential studies have suggested that hyperglycemic and dyslipidemia-induced biochemical derangements result in tissue hypoxia and up-regulation of VEGF [17,18]. The important anomalies related to mishandling of glucose and lipids leading to increased generation of advanced glycation and lipid peroxidation end products, oxidative stress, and failure of the body's antioxidant defense systems, ultimately invite inflammation, hypoxia, and increased VEGF secretion [17,18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been demonstrated by landmark studies that improving glycemic control reduces the risk of development and progression of DR, though there is no lower limit of glycemic control that is protective against the onset of retinopathy [15,16]. Our sequential studies have suggested that hyperglycemic and dyslipidemia-induced biochemical derangements result in tissue hypoxia and up-regulation of VEGF [17,18]. The important anomalies related to mishandling of glucose and lipids leading to increased generation of advanced glycation and lipid peroxidation end products, oxidative stress, and failure of the body's antioxidant defense systems, ultimately invite inflammation, hypoxia, and increased VEGF secretion [17,18].…”
Section: Discussionmentioning
confidence: 96%
“…Our sequential studies have suggested that hyperglycemic and dyslipidemia-induced biochemical derangements result in tissue hypoxia and up-regulation of VEGF [17,18]. The important anomalies related to mishandling of glucose and lipids leading to increased generation of advanced glycation and lipid peroxidation end products, oxidative stress, and failure of the body's antioxidant defense systems, ultimately invite inflammation, hypoxia, and increased VEGF secretion [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated by landmark studies that improving glycemic control reduces the risk of development and progression of DR, though there is no lower limit of glycemic control that is protective against the onset of retinopathy [ 15 , 16 ]. Our sequential studies have suggested that hyperglycemic and dyslipidemia-induced biochemical derangements result in tissue hypoxia and upregulation of VEGF [ 17 , 18 ]. The important anomalies related to mishandling of glucose and lipids leading to increased generation of advanced glycation and lipid peroxidation end products, oxidative stress, and failure of the body's antioxidant defense systems ultimately invite inflammation, hypoxia, and increased VEGF secretion [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our sequential studies have suggested that hyperglycemic and dyslipidemia-induced biochemical derangements result in tissue hypoxia and upregulation of VEGF [ 17 , 18 ]. The important anomalies related to mishandling of glucose and lipids leading to increased generation of advanced glycation and lipid peroxidation end products, oxidative stress, and failure of the body's antioxidant defense systems ultimately invite inflammation, hypoxia, and increased VEGF secretion [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation